Multi-object spectroscopy of stars in the CoRoT fields: I. Early-type stars in the CoRoT-fields IRa01, LRa01, LRa02 - Sebastian, Daniel; Guenther, E. W.; Schaffenroth, Veronika; Gandolfi, Davide; Geier, Stephan; Heber, Ulrich; Deleuil, Magali; Moutou, C. (Astronomy & Astrophysics, 2012)
Context. Observations of giant stars indicate that the frequency of giant planets is much higher for intermediate-mass stars than for solar-like stars. Up to now all known planets of giant stars orbit at relatively far distances from their host stars. It is not known whether intermediate-mass stars also had many close-in planets when they were on the main sequence, which were then engulfed when the star became a giant star. To understand the formation and evolution of planets it is therefore important to find out whether main-sequence stars of intermediate-mass have close-in planets or not. Aims. A survey for transiting planets of intermediate-mass stars would be ideal to solve this question, because the detection of transiting planets is not affected by the rapid rotation of these stars. With CoRoT it is possible to detect transiting planets around stars up to a spectral type B4V. As a first step for an efficient survey we need to identify intermediate-mass stars in the CoRoT-fields, which can then be used as an input list. Methods. To compile the input list we derived the spectral types of essentially all O, B and A stars down to 14.5 mag in the CoRoT fields IRa01, LRa01, LRa02 taken with the multi-object spectrograph AAOmega. We determined the spectral types by comparing the spectra with template spectra from a library. Results. In total we identify 1856 A and B stars that have been observed with CoRoT. Using multiple spectra of these stars, we find that the accuracy of the resulting spectral classification is 1.61 ± 0.14 sub-classes for A and B stars. Conclusions. Given the number of planets that have been detected in these fields amongst late-type stars, we estimate that there are one to four transiting planets of intermediate-mass stars waiting to be discovered. Our survey not only allows us to carry out a dedicated planet search programme but is also essential for any types of studies of the light curves of early-type stars in the CoRoT database. We also show that it would be possible to extend the survey to all fields that CoRoT has observed using photometrically determined spectral types. © 2012 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Planets and satellites: detection; Planets and satellites: formation; Stars: early-type; Surveys; Techniques: spectroscopic